Rhetoric of Prophet Abraham and Prophet Joseph Peace Upon Them - Nurbaini Futuhat Wulansari (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2023)
Rhetoric of da'wah will determine the success or failure of a "persuade" conveyed by preachers. The use of rhetorical sentences gives an impression of a "falseness" was actually used by Prophet Abraham and Prophet Joseph Peace Upon Them when preaching.This article proves to present one of the rhetorical models spoken by Prophet Abraham and Prophet Joseph Peace Upon Them. The research method used in this research is the library study method. This method was chosen because researchers are more able to explore related texts that contain the rhetoric of the preaching of the prophets. Prophet Abraham gave an example of his rhetoric when he destroyed obedient idols and Prophet Joseph gave an interpretation of dreams. It is this rhetoric that makes debaters or people who are enemies of them aware of the true truth through different ways between prophets from one another due to the conditions of the people of different times and conditions.